FUTURES PRICE AND TRADING VOLUME : EVIDENCE FROM MALAYSIA - Bakri, Abdul Karim; Zulkefly, Abdul Karim (UUM PRESS, 2011)
This paper examines the long- and short-run dynamic causality between the futures price and trading volume in the Malaysian equity market. The data of futures price, trading volume and spot price are in daily frequency, spanning from 2006 to 2009. By using ARDL cointegration and VECM causality tests, the findings revealed the existence of long-run relationship between futures price, volume and spot prices. In addition, there exists a short-run bidirectional causality relationship running between futures return-trading volume and futures return-spot return. Thus, the stock index futures market in Malaysia is not informational efficient.